Reliability-based optimal control of semi-rigid steel frames under simulated earthquakes using liquid column vibration absorbers. Issue 4 (3rd April 2021) - Rafiee, Amin; Hadidi, Ali; Farahmand Azar, Bahman
Abstract : Liquid column vibration absorbers (LCVAs) have been proved to be highly efficient in vibration suppression of buildings under earthquake and wind loads. This article proposes an efficient computational framework for reliability-based optimal design and placement of LCVAs in semi-rigidly connected buildings subjected to stochastic ground motions. The reduced function evaluations method is used as an efficient tool for structural reliability analysis, while a novel algorithm is proposed for efficient structural optimization. Excessive interstorey drifts of a building and absolute accelerations of its floors are considered as failure events in calculating the probability of failure of the building. The uncertainty regarding the characteristics of future earthquakes is accounted for by applying a probabilistic approach. The effects of pulse components of stochastic pulse-wise ground motions, fixity factor of semi-rigid beam-to-column connections and values of different parameters of LCVAs on the performance and safety of semi-rigidly connected steel-framed buildings are investigated.